YSZ Hollow Sphere Photonic Glasses: Tailoring Optical Properties for Highly Saturated Non‐Iridescent Structural Coloration. Issue 18 (30th May 2019) - Häntsch, Yen; Shang, Guoliang; Petrov, Alexander; Eich, Manfred; Schneider, Gerold A.
Abstract: Non‐iridescent structural colors can be obtained by the disordered arrangement of monodisperse spheres, a so‐called photonic glass (PhG), in which the structure is designed to reflect or transmit light at specific wavelengths depending on the desired color. PhGs are possible alternatives for conventional pigments due to their wide viewing angle, stability against photobleaching, and environment‐friendly fabrication. However, structural colors generated by common full‐sphere PhGs reported in the literature show only low saturation. The recently developed PhG structure based on yttria‐stabilized zirconia (YSZ) hollow spheres displays highly saturated blue structural color for tailored parameters. In this case, structural color originates from a sharp transition in the reflection spectrum generated by the specific design of the YSZ hollow sphere PhG fabricated via co‐deposition. Here, a systematic study of the parameters resulting in highly saturated structural color, namely YSZ shell thickness, pore size, and film thickness, is presented. This work shows that by tailoring these parameters, the sharpness, spectral position, and reflectance of the transition can be tuned individually. Based on the gained knowledge, YSZ hollow sphere PhG with tailored optical properties can be easily fabricated. Abstract : Highly saturated noniridescent blue structural color is developed based on the disordered arrangement of yttria‐stabilized zirconia hollow spheres. A systematic study revealing the structure–property relationship of this photonic glass regarding structural coloration is presented. By understanding the influence of shell thickness, pore size, and film thickness on the reflection, new insights into the fabrication of structural colors are obtained.